GW24-e3058 Acute Coronary Syndrome Patients with Type 2 Diabetes had Higher Healthcare Costs versus Patients without Diabetes in the US Population from 2006 to 2011. (1st October 2013) - Xu, Yaping; Cziraky, Mark; Luthra, Rakesh; Fisher, Maxine; Wilhelm, Ken; Power, Thomas; Reddy, Vanessa S
Abstract : Objectives: Acute coronary syndrome (ACS) contributes significantly to morbidity and mortality and represents an enormous economic burden to society. Type 2 diabetes (T2D) has been recognised as one of the major risk factors for ACS; however, there are limited published data quantifying the impact of T2D on healthcare costs, especially the long-term costs following ACS. This study evaluated the total and cardiovascular (CV)-related healthcare costs for ACS patients with T2D versus patients without diabetes. Methods: Patients with ≥ 1 ICD-9 code for acute myocardial infarction (410.xx) or unstable angina (411.1x) during hospitalisation were identified from the HealthCore Integrated Research Database (HIRD SM ) between January 2006 and September 2011. The first ACS hospitalisation date was defined as the index event date. T2D patients were selected if ≥ 2 claims for T2D (250.x0, 250.x2) at least 30 days apart; or ≥ 1 claim for T2D and ≥ 1 claim for oral or injectable anti-diabetics; or ≥ 2 prescriptions of oral anti-diabetics or glucagon-like peptide 1 medications. Those with no evidence of a type 1 or 2 diabetes diagnosis claim (250.xx) in the study period were identified as ACS patients without diabetes. Patients with < 12 months plan eligibility pre- and post-index ACS or age < 18 years were excluded. Total and CV-related healthcare costs following the index ACS event were evaluated in patients with T2D and without diabetes, for 1, 2 and 3 years, respectively, adjusting for baseline differences including demographic characteristics, comorbidities, treatment utilisation and index ACS characteristics. Results: Of the 140, 903 ACS patients identified, 38, 553 (27%) and 81, 845 (58%) patients have been selected into the ACS with T2D and without diabetes cohorts, respectively. Patients with T2D versus without diabetes were older (mean age 68.2 versus 65.6 years, respectively) and had higher mean baseline comorbidities (Deyo-Charlson Index score 3.15 versus 1.11, respectively). Mean (median) length of stay of the index ACS hospitalisation was longer in patients with T2D versus without diabetes (7.62 [4.00] versus 5.20 [3.00] days, respectively). Adjusted mean (median) 1-, 2- and 3-year post-index total and CV-related costs for the T2D cohort were significantly higher than those without diabetes. After adjusting for baseline differences, compared to non-diabetes, ACS patients with T2D had significant 14.4%, 16.2% and 14.8% increased total annual costs at 1, 2 and 3 years, respectively. Conclusions: T2D patients have increased total and CV-related healthcare costs at 1, 2 and 3 years post-ACS event as compared with non-diabetes patients. These results provide further confirmation that new therapies directed specifically at T2D patients with ACS are needed, not only to improve the quality of care, but also to help reduce the cost of care.